Continuous Cash Flow Modeling for Economic Evaluation and Risk Analysis in Mine Planning Using Monte Carlo Simulation - Ahmed, Haitham M.; Adewuyi, Sefiu; Ahmed, Hussin M. A. (Journal of King Abdulaziz University: Engineering Sciences, 2024)
The discrete cash flow (DCF) model is usually used to estimate the net present value (NPV) of most projects. However, the model produces results that could be short of reality, especially for projects with high uncertainties that last for decades, as in mining projects. Hence, this paper develops a Continuous Cash Flow (CCF) model for the economic evaluation of mining projects. The model is used for the economic feasibility of a gold mine project in Saudi Arabia. The dynamic DCF model is also used for the same project and obtained results from both models were simulated using the Monte Carlo technique. Results show that the CCF model produces lower NPV values than the DCF. The developed model could be an alternative approach to determining the expected NPV in mine projects.